2014
DOI: 10.5897/ajb2013.13200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth and yield of some high-and low-cyanide cassava genotypes in acid ultisols of south eastern Nigeria

Abstract: Thirty-eight high and low cyanide cassava genotypes were evaluated for growth and yield. The experiment was fitted in a randomized complete block design with three replications. Analysis of variance (ANOVA) revealed significant difference (P<0.05) in growth and yield parameters, indicating strong genetic variations among the genotypes. Significant (P<0.05) highest average storage root weight of 1.5 and 1.8 kg were obtained from TMS 94/0035 (high cyanide cassava genotype) and TMS 98/0505 (low cyanide cassava ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
3
3
1
Order By: Relevance
“…Bitter cassava exhibited higher tolerance to CMD due to the presence of the cyanogenic glycosides while sweet cassava was more susceptible to CBB resulting in moderate bulking rate and fresh root yield that showed non-significant difference between the two groups. The findings contradicted previous studies by Wilson and Dufour (2002) and Okpara et al. (2014) in which they asserted that bitter cassava cultivars yielded more than sweet (low cyanide content) cultivars on the plausible inference that bitter cultivars had the tendency to exhibit stronger resistance to diseases and pests than sweet cultivars due to the high presence of cyanogenic glycosides thereby resulting in higher root yields.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Bitter cassava exhibited higher tolerance to CMD due to the presence of the cyanogenic glycosides while sweet cassava was more susceptible to CBB resulting in moderate bulking rate and fresh root yield that showed non-significant difference between the two groups. The findings contradicted previous studies by Wilson and Dufour (2002) and Okpara et al. (2014) in which they asserted that bitter cassava cultivars yielded more than sweet (low cyanide content) cultivars on the plausible inference that bitter cultivars had the tendency to exhibit stronger resistance to diseases and pests than sweet cultivars due to the high presence of cyanogenic glycosides thereby resulting in higher root yields.…”
Section: Discussioncontrasting
confidence: 99%
“…(2012) in their various works reported strong and positive correlation between CMD and CBB disease incidence and severity depending on season. Further correlation results based on cyanide levels of the genotypes from the study corroborate similar works by Ntawuruhunga and Dixon (2010), Okpara et al. (2014) and Rao et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicated that farmers preferred sweet and high starch taste qualities which may be linked to pathogen presence and spread culminating in disease incidence and severity. The sweet varieties were more susceptible to CBSV and CMV infections than the bitter varieties documented by Okpara et al (2014) and Nakabonge et al (2017). The findings support those of Nakabonge et al (2017), where preference for cultivars was determined by a number of factors including sweet taste, good cooking quality, high yielding, early maturing, high marketability, good storability in the ground and tolerance to diseases among others.…”
supporting
confidence: 69%
“…Several studies on other tuber crops tend to show similar results. For example, Okpara et al observed no correlation response between number of leaves and storage root yield in cassava [31]. Similarly Bassey established no significant correlation between number of leaves per vine and fresh tuber yield in sweetpotato.…”
Section: Discussionmentioning
confidence: 98%